Analisis Perkembangan Perkebunan Kelapa Sawit Provinsi Sumatera Utara - Purba, Markus Buha Amando; Nurcahyani, Marizha (AGRISAINS: Jurnal Ilmiah Magister Agribisnis, 2025)
This article aims to analyze the potential advantages of the palm oil plantation sector in North Sumatra Province and evaluate its level of specialization and localization. The study focuses on assessing these aspects to support the sector's optimal development. Data were collected from the Central Bureau of Statistics and other relevant institutions and analyzed using qualitative and quantitative approaches, including Location Quotient (LQ) analysis, Localization Coefficient (α) analysis, and Specialization Coefficient (β) analysis with the aid of Microsoft Excel software. The findings indicate that from 2019 to 2022, palm oil plantations in North Sumatra served as a base sector in terms of land area and production (LQ 1) but have not yet become a primary sector in labor absorption (LQ 1). The localization coefficient (α 1) suggests that palm oil plantations are spread across multiple districts/cities rather than being concentrated in a single area. Additionally, the specialization coefficient (β 1) reveals that no district or city specializes in palm oil plantation management.